2018
DOI: 10.3389/fchem.2018.00344
|View full text |Cite
|
Sign up to set email alerts
|

Polyketides From the Endophytic Fungus Cladosporium sp. Isolated From the Mangrove Plant Excoecaria agallocha

Abstract: Five new polyketides (2–6) and ten known compounds (1 and 7–15) were obtained from the fermentation products of the endophytic fungus Cladosporium sp. OUCMDZ-302 with the mangrove plant, Excoecaria agallocha (Euphorbiaceae). The new structures of 2–6 were established on the basis of ECD, specific rotation and spectroscopic data as well as the chemical calculation. Compound 7 showed cytotoxicity against H1975 cell line with an IC50 value of 10.0 μM. Compounds 4 and 8–10 showed radical scavenging activity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The new compounds 1 – 5 and 7 exhibited α-glucosidase inhibitory activity. Combined with bioactive NPs from mangrove-derived fungi [ 34 , 35 , 36 , 37 , 38 ], the results indicated that fungi living in the salt-tolerant plants are an important biological resources for new and bioactive NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The new compounds 1 – 5 and 7 exhibited α-glucosidase inhibitory activity. Combined with bioactive NPs from mangrove-derived fungi [ 34 , 35 , 36 , 37 , 38 ], the results indicated that fungi living in the salt-tolerant plants are an important biological resources for new and bioactive NPs.…”
Section: Discussionmentioning
confidence: 99%
“…We should also note the mangrove endophyte Cladosporium sp. [116], the source of a new glycosylated chromone (78) and the previously known 7-Oα-D-ribosyl-5-hydroxy-2-propyl-chromone (79) [117], which showed cytotoxic properties.…”
Section: Quinonesmentioning
confidence: 99%
“…[136], endophyte Pluchea indica. This strain was the source of three new isocoumarins, i.e., dichlorodiaportin (116), desmethyldichlorodiaportin (117), and desmethyldichlorodiaportinol (114), along with several other well-known analogs, i.e., dichlorodiaportinol (115) [137], desmethyldichlorodiaportin (119) [138], and dichlorodiaportin (120) [139,140]. Other isocoumarins with antibiotic activity turned out to have been be previously described.…”
Section: Other Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation
“…HNWSW-1 was isolated from the healthy tree root of Ceriops tagal collected from the Dong Zhai Gang Mangrove Reserve in Hainan. The secondary metabolites of the genus Cladosporium have been mainly reported as polyketides derivatives, such as fatty acids [12], macrolides [13,14,15], pyrones [16,17,18], binaphthyl derivatives [19,20], α-pyridone [21] and tetramic acid derivatives [22,23]. Subsequent chemical investigations on the EtOAc extract of its fermentation cultures led to the isolation of cladosporitins A ( 1 ) and B ( 2 ), which contain the succinimide unit linked to phenol and decalin fragments.…”
Section: Introductionmentioning
confidence: 99%